Effects of Aggregate Structure and Dimension of Carbon Nanotubes on the Mechanical, Electrical and Thermal Properties of Rubber Composites - Kim, Sung-Woo; Jeong, Ho-Kyun; Kang, Yong-Gu; Han, Min-Hyeon (Asian Journal of Chemistry, 2013)
A tyre tread compound, showing good performance and high electrical conductivity, was prepared with a high silica loading and a low loading of multi-wall carbon nanotube in order not to sacrifice the original mechanical properties of the rubber compound. We fabricated styrene-butadiene rubber/natural rubber composites containing carbon black as a general filler and two types of multi-wall carbon nanotube with different structure and dimension, entangled carbon nanotube with short length (<10 μm) and parallel-aligned carbon nanotube bundles with a long length (<120 μm) as a specific filler. The incorporation of the aligned multi-wall carbon nanotube into the high silica rubber compound, even at low loading (0.5 phr), improved the static dissipation to a level that could meet the requirements (<108 W) for tyres without a measurable decrease in the physical and dynamic properties. The abrasion resistance was also enhanced considerably by 15 % or more.